2012
DOI: 10.1017/s0007114512004205
|View full text |Cite
|
Sign up to set email alerts
|

In vitrofermentation of commercial α-gluco-oligosaccharide by faecal microbiota from lean and obese human subjects

Abstract: The fermentation selectivity of a commercial source of a-gluco-oligosaccharides (BioEcolians; Solabia) was investigated in vitro. Fermentation by faecal bacteria from four lean and four obese healthy adults was determined in anaerobic, pH-controlled faecal batch cultures. Inulin was used as a positive prebiotic control. Samples were obtained at 0, 10, 24 and 36 h for bacterial enumeration by fluorescent in situ hybridisation and SCFA analyses. Gas production during fermentation was investigated in non-pH-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…They can also be branched in structure. Commercial GlOS products have been shown to be selective for bifidobacteria and bacteroides with a decrease in Faecalibacterium prausnitzii using in vitro faecal batch cultures [38] and bacterial counting using group-specific fluorescent gene probes. Whilst an increase in bifidobacteria would be considered as a health-positive change, a decrease in F. prausnitzii might not be desirable as this species is attracting interest as an anti-inflammatory component of the gut microbiota [39 ].…”
Section: Novel Candidate Prebioticsmentioning
confidence: 99%
“…They can also be branched in structure. Commercial GlOS products have been shown to be selective for bifidobacteria and bacteroides with a decrease in Faecalibacterium prausnitzii using in vitro faecal batch cultures [38] and bacterial counting using group-specific fluorescent gene probes. Whilst an increase in bifidobacteria would be considered as a health-positive change, a decrease in F. prausnitzii might not be desirable as this species is attracting interest as an anti-inflammatory component of the gut microbiota [39 ].…”
Section: Novel Candidate Prebioticsmentioning
confidence: 99%
“…The tubes were kept at 4°C for approximately 2 h to dissolve the substrates before initiating fermentations. The inoculate were prepared as described by Sarbini, Kolida, Gibson, and Rastall (2012). Before inoculation, the tubes were pre-warmed in a 37°C water bath for 30 min, and then each vessel was inoculated with 1 mL of fresh faecal slurry with the upper space of each tube filled with pure N2 under normal pressure.…”
Section: In Vitro Fermentation Of Polysaccharidesmentioning
confidence: 99%
“…Sarbini et al (2013) reported that commercial α-gluco-oligosaccharides significantly increased the Bifidobacterium sp. population compared with the control (inulin) and the fermentation of α-glucooligosaccharides produced less gas than inulin.…”
Section: Introductionmentioning
confidence: 99%